Expressões de reconhecimento social de usuários de um serviço de proteção social especial do SUAS - Sant’Anna, Cláudia Oliveira (2018)
The present dissertation has as objective to know and understand the perception of the users related to their recognition in the attention offered by a Social Assistance Service. It is the approach related to the institutional reception service, understanding the manner the social recognition expressions are made in the trajectory of attention to users, knowing the expressions of social deprotection which leads them to access a special social protection service of high complexity in the social assistance, as well identifying with families the acquisitions recognized as answers to their needs. The analytical route performed in this study demanded deepening about the scope of an institutional reception service to children from their historical evolution in Brazil and particularly the impact of legalization of social rights to the Brazilian people viable through the Federal Constitution of 1988 against the objective of Child and Adolescent Statute (ECA) and the Social Assistance Unique System (SUAS). In the course of this research, with the support of several authors it was possible to show the event which occurred historically in the legal area in overcome the attention to children in Brazil in the field of charity, favor and goodwill, supported by the value judgement for the perspective of attentions in the social right condition. To the interviews and field surveys were selected five families who had as reason of institutional reception of children the negligence or the abandonment. The study plunged in the relationship among the family, the child and the service, and being synthesized in three moments: the triggering situation of the reception: reason, complainant, procedure of the tutelary council and the judge, link with some social assistance service; the time of attention to the child in the reception and the manner of relation to the family made by the service and verified in the file records and the users’ speeches highlighting the records on: the attentions supported by the service and its direct repercussion in the life of the children, teenagers and families; the relation with the families and of their access to the public attentions and services which they would be entitled to; the ways in which social security was ensured to the children and teenagers; of activies that the children had the opportunity to experience during the institutional reception; and finally the moment of post-dismissal of the child of the reception service. It is a qualitative research whose essence was the quest to listen to users, which represents the most important step in this study, which allowed to know the meaning attributed by users to the attention of an institutional reception service